A Decision-Theoretic Model of Behavior Change - Matsumori, Kaosu; Iijima, Kazuki; Koike, Yasuharu; Matsumoto, Kenji (Frontiers in Psychology, 2019)
Undesirable habitual or addictive behaviors are often difficult to change. This issue of “behavior change” has long been studied in various research fields. Several models for behavior change have converged on the hypothesis that attitudes, norms, and self-efficacy are the important determinants of intentions and behavior. In order to improve the accuracy of the models for behavior change, some researchers have tried to combine behavioral economic models with existing models for behavior change. However, these attempts have failed because the existing models of behavior change are not consistent with Expected Utility Theory (EUT), which underlies a variety of behavioral economic models. In the present paper, we clarify the corresponding components between existing models for behavior change and EUT, and propose a new behavior change model, Decision-Theoretic Model of behavior change (DTM), which is a natural extension of ordinary EUT.